Greenhouse gas emissions under winter wheat‐based organic and conventional crop productions. Issue 5 (5th April 2021) - Sainju, Upendra M.; Hatfield, Patrick G.; Ragen, Devon L.
Abstract: Information on greenhouse gas (GHG) emissions in organic crop production using sheep ( Ovis aries L.) grazing to control weeds is lacking. We examined GHG emissions from May 2013 to April 2016 under wheat ( Triticum aestivum L.)‐based sequences in organic and conventional crop productions in the northern Great Plains. Organic crop production included sheep grazing to control weeds without N application (OCP) and conventional crop production included herbicides, pesticides, and N applications (CCP). Cropping sequences in a 5‐yr rotation of safflower ( Carthamus tinctorius L.)/sweetclover cover crop [ Melilotus officinalis (L.) Lam.]–sweetclover cover crop–winter wheat–lentil ( Lens culinaris L.)–winter wheat were lentil after winter wheat (L–W), winter wheat after sweetclover cover crop (W–C), and winter wheat after lentil (W–L). The CO2 and N2 O fluxes peaked immediately after tillage, planting, fertilization, intense precipitation, and snowmelt, but CH4 uptake increased in the autumn. Cumulative CO2 flux was lower with OCP than CCP for W–C in 2014–2015 and for W–L in 2015–2016. Cumulative N2 O flux was also lower with OCP than CCP for W–C in 2014–2015, but was greater with OCP than CCP for L–W in 2015–2016. Treatments did not affect cumulative CH4 flux. The global warming potential (GWP) was lower with OCP than CCP for W–C in 2014–2015 and for W–L in 2015–2016. Organic crop production using sheep grazing with no chemical input reduced GHG emissions under winter wheat following clover cover crop or lentil compared with conventional crop production using chemical inputs under lentil following winter wheat. Core Ideas: Information on greenhouse gas emissions under organic and conventional crop productions is limited. Greenhouse gas emissions under wheat‐based organic and conventional crop productions was examined. Organic wheat production reduced CO2 and N2 O emissions compared with conventional crop production. Wheat following lentil and clover increased CO2, but lentil following wheat increased N2 O emissions. Wheat‐based organic crop production can reduce greenhouse gas emissions.